Highly selective palladium–benzothiazole carbene-catalyzed allylation of active methylene compounds under neutral conditions - Monopoli, Antonio; Cotugno, Pietro; Zambonin, Carlo Giorgio; Ciminale, Francesco; Nacci, Angelo (Beilstein Journal of Organic Chemistry, 2015)
The Pd–benzothiazol-2-ylidene complex I was found to be a chemoselective catalyst for the Tsuji–Trost allylation of active methylene compounds carried out under neutral conditions and using carbonates as allylating agents. The proposed protocol consists in a simplified procedure adopting an in situ prepared catalyst from Pd2dba3 and 3-methylbenzothiazolium salt V as precursors. A comparison of the performance of benzothiazole carbene with phosphanes and an analogous imidazolium carbene ligand is also proposed.
Keywords: active methylene compounds; allylic carbonates; Pd–benzothiazol-2-ylidene complex; Tsuji–Trost allylation